Uninsured risk, stagnation, and fiscal policy - R. Anton Braun; Tomoyuki Nakajima (Federal Reserve Bank of Atlanta, 2016)
Japan is in the midst of a protracted spell of depressed economic activity. Japan's economic stagnation has occurred against a background of rising earnings risk. Occupational stability is falling as routine occupations disappear and implicit lifetime employment guarantees are gradually disappearing. At the same time, earnings in some high-skilled occupations have continued to grow. The resulting polarization in earnings has been accompanied by an increase in wealth inequality. This paper develops a framework that relates these observations. In our model, an increase in uninsured earnings risk depresses output and increases wealth inequality. We then analyze the efficacy of alternative fiscal measures in terms of their ability to increase economic activity, reduce wealth inequality, and improve welfare. A reduction in the tax rate on capital achieves all of these objectives.
Keywords: E13; E16; D31; 330; economic stagnation; wage polarization; wealth inequality